2012
DOI: 10.1186/1471-2377-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine is neuroprotective in an in vitro model for traumatic brain injury

Abstract: BackgroundThe α2-adrenoreceptor agonist dexmedetomidine is known to provide neuroprotection under ischemic conditions. In this study we investigated whether dexmedetomidine has a protective effect in an in vitro model for traumatic brain injury.MethodsOrganotypic hippocampal slice cultures were subjected to a focal mechanical trauma and then exposed to varying concentrations of dexmedetomidine. After 72 h cell injury was assessed using propidium iodide. In addition, the effects of delayed dexmedetomidine appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 29 publications
1
84
0
4
Order By: Relevance
“…These properties may decrease delirium, both by avoiding deliriogenic opiates and sedatives but also by more direct neuroprotective mechanisms 60. This has led to several clinical studies involving dexmedetomidine in the ICU.…”
Section: Preventionmentioning
confidence: 99%
“…These properties may decrease delirium, both by avoiding deliriogenic opiates and sedatives but also by more direct neuroprotective mechanisms 60. This has led to several clinical studies involving dexmedetomidine in the ICU.…”
Section: Preventionmentioning
confidence: 99%
“…Recent studies have indicated that dexmedetomidine also exhibits neuroprotective effects against ischemic injury 26 and promotes the survival of nervous tissue that has suffered traumatic injury 27 . However, a study in neutrophils reported that treatment with a high concentration of dexmedetomidine 100 ng / ml ; 499.3 nM accelerated apoptosis, whereas a clinically relevant concentration of dexmedetomidine 1 ng / ml ; 4.993 nM did not affect neutrophil apoptosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…LC therefore advocates the use of anti-hypertensive treatment (beta-1 blockade, alpha-2 agonists, angiotensin II antagonist) (Asgeirsson et al, 1994, 1995, Grände, 2006. It has been shown that beta-blockade in sTBI patients is independently associated with improved survival (Cotton et al, 2007;Inaba et al, 2008) and that alpha-2 agonist effectively reduces blood pressure in sTBI patients (Kariya et al, 1999) and is neuroprotective in an in vitro model for traumatic brain injury (Schoeler et al, 2012). Beta-blockade has also a documented protective effect on the cardiovascular system after a sTBI (Cruickshank et al, 1987).…”
Section: Treatment Of Icpmentioning
confidence: 99%